Oral and dental manifestations of celiac disease in children: a case-control study - Farah A. Alsadat; Najlaa M. Alamoudi; Azza A. El-Housseiny; Osama M. Felemban; Faisal M. Dardeer; Omar I. Saadah (BMC, 2021)
Abstract Background Celiac disease (CD) is an immune-mediated enteropathy. CD may also involve complications with the oral cavity, which can result in various dental and oral pathologies. There are currently a limited number of studies on the oral manifestation of CD. This study aims to compare the oral manifestations of children with CD against healthy controls in Saudi Arabia. Materials and methods This study includes 208 children aged 6-14 years, distributed equally into CD patients and healthy controls. A parent completed and validated the interview questionnaire, which included the child's personal information and medical history. A dental examination was undertaken to measure possible recurrent aphthous stomatitis (RAS), dental enamel defects (DEDs), dental caries experience, and dental malocclusion. Data were analyzed using descriptive statistics and bivariate and multivariate analysis. Results Two hundred and eight participants were included (104 CD patients and 104 controls). The mean age for CD patients was 10.67 ± 2.39 years and 10.69 ± 2.36 for the healthy controls. CD children had more RAS than controls (42.3% vs. 15.4%, P < 0.001) (OR = 4.03, 95% CI = 2.09-7.81) and more DEDs than healthy controls (70.2% vs. 34.6%, P < 0.001) (OR = 4.45, 95% CI = 2.48-7.97). No significant difference was found in the frequency of malocclusion between cases and controls. Conclusion Saudi Arabian children with CD had a greater number of clinical findings of RAS and DEDs than healthy controls. Pediatric dentists should consider the possibility of CD in child patients presenting with RAS or DEDs.